2006
DOI: 10.1002/med.20083
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of progesterone receptor ligands

Abstract: Progesterone is one of the first nuclear receptor hormones to be described functionally and subsequently approached as a drug target. Because progesterone (1) affects both menstruation and gestation via the progesterone receptor (PR), research aimed at modulating its activity is usually surrounded by controversy. However, ligands for PR were developed into drugs, and their evolution can be crudely divided into three periods: (1) drug-like steroids that mimic the gestational properties of progesterone; (2) drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 102 publications
0
22
0
1
Order By: Relevance
“…2 is the mechanism of action for an array of medications and continues to be a fertile area for research, with special focus on the development of mixed profile compounds (1)(2)(3). Mixed profile modulators of PR are characterized by decreased transcriptional activity compared with full agonists and increased transcriptional activity compared with full antagonists.…”
Section: Modulation Of the Progesterone Receptor (Pr)mentioning
confidence: 99%
“…2 is the mechanism of action for an array of medications and continues to be a fertile area for research, with special focus on the development of mixed profile compounds (1)(2)(3). Mixed profile modulators of PR are characterized by decreased transcriptional activity compared with full agonists and increased transcriptional activity compared with full antagonists.…”
Section: Modulation Of the Progesterone Receptor (Pr)mentioning
confidence: 99%
“…This makes them attractive pharmaceutical targets. Although SRs show exquisite selectivity for their endogenous hormones, SR-targeting drugs tend to be promiscuous and cause many off-target side effects (10,11). This is because SRs, consisting of the estrogen receptor, progesterone receptor (PR), androgen receptor (AR), mineralocorticoid receptor (MR), and glucocorticoid receptor (GR), descended from a common ancestor Ͼ500 million years ago (see Fig.…”
mentioning
confidence: 99%
“…Clashes between Met 909 and ligands are likely to destabilize helix-12 (21), which results in a reduced agonistic response. It has even been suggested that the degree of clash with Met 909 might correspond directly to the reduction in agonism (2), but this has yet to be shown categorically.…”
mentioning
confidence: 99%